Protective coatings for ceramic superplastic forming dies: An initial study on protective coating performance: Schutzbeschichtungen für keramische superplastische Formgebungswerkzeuge: Eine erste Studie zur Schutzbeschichtungsleistung. Issue 10 (19th October 2017) - Staiano, A.; Ion, W.; O'Hare, L.; Zuelli, N.
Abstract: Superplastic forming is an advanced manufacturing process, typically restricted to low volume and high value products. Refractory ceramics are a low cost option to substitute the high temperature resistant steels and other alloys conventionally used in superplastic forming dies, but their brittle nature is a limiting factor for most superplastic forming applications. Suitable surface coatings have shown a significant effect on wear resistance and can be employed to improve the ceramic performance in terms of tool life. This paper focuses on an initial study on protective coatings for superplastic forming ceramic dies to evaluate their effectiveness under superplastic forming conditions. Tests are conducted using a dedicated test rig built where the die‐blank interaction under superplastic forming conditions is replicated at laboratory scale. Two coating materials are tested and surface wear is compared with the uncoated surface of a particle‐reinforced fused silica refractory superplastic forming ceramic die. Results show that the selected coating materials have poor protective performance in comparison with the uncoated ceramic die, but they demonstrate the ability to assess protective coatings performance under superplastic forming conditions at a laboratory scale.